Linguistic diversity and communication dynamics an in-depth study of Phatic expressions in Bima - Alek Alek; Umar Abdullah (Indonesian Journal of Applied Linguistics, 2023)
Phatic expressions serve a vital role in daily communication, fostering the strengthening of social bonds and the maintenance of interpersonal relationships among conversational participants. Despite their significance, a comprehensive investigation into phatic expressions in regional Indonesian languages remains notably lacking. To address this research gap, our study delves into the diverse forms and functions of phatic expression within the Bima language (BL). Employing a qualitative approach with a descriptive research design, conversational interviews were conducted involving five participants, leading to the identification of fourteen distinct phatic utterances in BL. These expressions encompassed -ra, -na, -ku, -pu, rau, ke, ka, kan, rauja, oe, ha, ah, sih, and poda. Findings reveal that these phatic expressions serve a multitude of functions, encompassing affirmation, validation, explanation, expressions of surprise, conveying irritation, signaling uncertainty, emphasizing intensity, and issuing commands. Notably, the category of phatic expressions for affirmation exhibited the greatest diversity, featuring six distinct expressions. From a linguistic perspective, the use of this rich array of phatic expressions plays a pivotal role in maintaining seamless communication among speakers, contributing significantly to the fluidity of conversation. This study carries important pedagogical implications for language educators, particularly in Indonesia and regions where BL is spoken. Educators can enhance their students' linguistic repertoire, particularly in the context of the Bima language. Furthermore, by shedding light on the intricacies of phatic expression in BL, this research contributes to a broader exploration of language diversity and its sociolinguistic significance, further strengthening the documentation and preservation of regional languages.